The United States Constitution - Vile, J. author. aut Link
XI, 203 p.
Keywords: This book examines the U.S. Constitution by focusing on its origins in Western political thought and its organization and subsequent amendments. It describes the document as a series of choices among alternative governmental institutions that are designed to provide national security and secure ordered liberty.